Legal Protection of Minority Groups within Patriarchal Structures: The Rights of Women and Children Post-Divorce - Alim, Firmansyah Pratama; Maripah, Emma; Kolopita, Abdul Fajri (Kawanua International Journal of Multicultural Studies, 2025)
Divorce produces significant impacts on women and children as minority groups within patriarchal structures, particularly within Indonesia's plural legal system that integrates Islamic law, national law, and social practices. This research aims to analyze legal protection mechanisms for women and children as minority groups post-divorce in the Muslim community of Manado City, identify structural patriarchal factors that hinder the fulfillment of rights, analyze the intersectionality of oppression within the plural legal system, and evaluate the effectiveness of existing protection mechanisms. Using a descriptive qualitative approach, this empirical juridical research integrates a framework for minority studies and structural patriarchal analysis. Primary data were obtained from 106 talaq divorce cases at Manado Religious Court in 2021, focusing on 15 reconvention cases and 46 complaint cases at the UPTD for Women and Child Protection. Data collection through document study, observation, and in-depth interviews was analyzed using thematic analysis. As many as 85.8% of cases were decided in absentia without the wife's presence, reflecting systemic marginalization. Hindering factors include limited legal knowledge, economic dependency, masculinity construction that avoids responsibility, and institutional monitoring vacuums. The reconvention mechanism shows 66.7% success, but is limited by unequal accessibility. Legal protection for women and children requires systemic transformation, integrating minority rights perspectives through strengthening integrated databases, rights-based legal aid, Family Court Monitoring Units, and intersectionality-based capacity building for law enforcement.